Pengaruh Pengendalian Internal, Moralitas Individu, dan Tingkat Religius Terhadap Kecenderungan Kecurangan Akuntansi - Siela Saadatul Laili; Maslichah Maslichah; Afifudin Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2023)
The purpose of this study is to determine the influence of internal control variables, individual morality and religious level affect the tendency of accounting fraud. The population in this study are employees of PT. Bank BRI Martadinata Branch Office in Malang City. Determination of the sample in this study was carried out by probability random sampling. This research is a correlation research and data collection method are done by using a questionnaire method. In this study using statistical data analysis techniques in the form of multiple linear regression analysis the tests used are instrument tests, normality tests, classical assumption tests, hypothesis tests. The results of the study stated that the variables of internal control, individual morality, and religious level had a simultaneous influence on the dependent variable, namely the tendency of accounting fraud. Internal control variables partially have a negative effect on accounting fraud tendencies. Individual morality variable partially has no effect on the prevention of accounting fraud tendencies. Variable religious level partially has a negative effect on the tendency of accounting fraudKeywords: Internal control, individual morality, religious level and accounting fraud tendency